2018
DOI: 10.1109/jsen.2018.2869273
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Microfiber-Assisted Mach–Zehnder Interferometer for Microfluidic Highly Sensitive Measurement of Salinity

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…OFOF bio-chemical sensors based on MZI have been investigated for several decades, and various types of structures have been reported, including microcavities, [215,216] microfibers, [217][218][219][220][221] and other types of fibers. Other types of fibers include thin-core fiber, [222] TCF, [223] HTCF, [45,46] dual sidehole fiber (DSHF).…”
Section: Structures and Sensing Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…OFOF bio-chemical sensors based on MZI have been investigated for several decades, and various types of structures have been reported, including microcavities, [215,216] microfibers, [217][218][219][220][221] and other types of fibers. Other types of fibers include thin-core fiber, [222] TCF, [223] HTCF, [45,46] dual sidehole fiber (DSHF).…”
Section: Structures and Sensing Applicationsmentioning
confidence: 99%
“…On the one hand, the microfluidic channels can protect the fragile microfiber from the interference of surrounding environment, and on the other hand, it can furnish micro/nano-level samples for the microfiber, thereby assisting the microfiber to achieve a highly sensitive microfluidic measuring with good stability and reproducibility. [104] Depending on different sensing schemes, MZIs based on microfibers can be classified into four types: MZI based on biconical taper fiber, [220,226,227] MZI based on square-microfiber, [228] microfiber-assisted MZI (MAMZI), [85,219,221] and microfiber-capillary MZI. [95,97] Biconical taper microfibers, with diameters ranging from a few hundred nanometers to a few microns, are typically formed by heating with flame, electric or CO 2 laser and drawing.…”
Section: Mach-zehnder Interferometer Based On Microfibermentioning
confidence: 99%
“…Their hand-held microfluidic device was calibrated to detect conductivities in the range of 0.33–14.64 mS/cm, corresponding to relatively high salt levels of 165–7320 ppm, which is not suitable for drinking water monitoring. In another effort, Xie et al 27 presented a salinity sensor based on integrating microfluidics and optical fiber-assisted Mach–Zehnder interferometry. The study showed a high sensitivity detection for a 40–31000 ppm range of NaCl but was inept below 40 ppm, which is needed in the drinking water application.…”
Section: Introductionmentioning
confidence: 99%
“…NTERFEROMETRIC fiber sensors (IFSs) are widely used for measuring external environmental parameters, including gas refractive indices [1], temperature [2,3,4], strain [5,6], salinity [7], glucose [8], force [9] and respiration [10], because of their many advantages, such as low cost, simple fabrication, small size, anti-electromagnetic interference and high sensitivity/resolution. Generally, IFSs can simultaneously measure dual parameters [11,12].…”
Section: Introductionmentioning
confidence: 99%